The mechanism of bifonazole-induced [Ca2+]i rises and non-Ca2+-triggered cell death in PC3 human prostate cancer cells. (December 2014) - Cheng, Jin Shiung; Chou, Chiang-Ting; Liang, Wei-Zhe; Kuo, Chun-Chi; Shieh, Pochuen; Kuo, Daih-Huang; Jan, Chung-Ren
Abstract Bifonazole is an antifungal drug widely used for treating skin diseases. The effect of bifonazole on physiology of cancer cells is unclear. The effect of bifonazole on cytosolic free Ca2+ concentrations ([Ca2+]i) and viability in PC3 human prostate cancer cells was explored. The Ca2+-sensitive fluorescent dye, fura-2, was applied to measure [Ca2+]i. Bifonazole at concentrations of 5–30 µM induced a [Ca2+]i rise in a concentration-dependent manner. The response was reduced by 50% by removing extracellular Ca2+. Bifonazole-evoked [Ca2+]i rise was not altered by nifedipine, econazole, SK&F96365 and protein kinase C activator, but was inhibited by 75% by GF109203X, a protein kinase C inhibitor. In Ca2+-free medium, treatment with the endoplasmic reticulum Ca2+ pump inhibitor 2, 5-di-tert-butylhydroquinone (BHQ) nearly abolished bifonazole-evoked [Ca2+]i rise. Conversely, treatment with bifonazole abolished BHQ-evoked [Ca2+]i rise. Inhibition of phospholipase C with U73122 abolished bifonazole-induced [Ca2+]i rise. At 30–100 µM, bifonazole decreased cell viability concentration-dependently, which was not reversed by chelating cytosolic Ca2+ with 1, 2-bis(2-aminophenoxy)ethane-N, N, N″, N′-tetraacetic acid/acetoxy methyl. Annexin V/propidium iodide staining data suggest that bifonazole (30–100 µM) induced apoptosis concentration-dependently. Together, in PC3 human prostate cancer cells, bifonazole induced [Ca2+]i rises by inducing phospholipase C- and protein kinase C-dependent Ca2+ release from the endoplasmic reticulum and Ca2+ influx via non-store-operated pathways. Bifonazole induced cell death that might involve apoptosis.